Staged open surgery for bicuspid aortic valve regurgitation and coarctation of the aorta in a Jehovah’s witness - Sumi, Kohei (BMC Cardiovasc Disord, 2020)
BACKGROUND: Jehovah’s Witnesses refuse allogeneic blood transfusions, which makes cardiovascular surgery challenging. Surgeons must minimize blood and fluid loss within one procedure. CASE PRESENTATION: We herein describe a 17-year-old male Jehovah’s Witness with bicuspid aortic valve regurgitation and coarctation of the aorta. The procedures were performed in the following order: aortic valve replacement combined with Nick’s aortic root enlargement, right axillary artery–bilateral external iliac artery bypass, and distal arch–descending aorta bypass. CONCLUSIONS: Axillary artery–bilateral external iliac artery bypass maintained distal perfusion and reduced the amount of heparin during distal arch–descending aorta bypass surgery.